Covalent linkage of the DNA repair template to the CRISPR-Cas9 nuclease enhances homology-directed repair - Natasa Savic; Femke CAS Ringnalda; Helen Lindsay; Christian Berk; Katja Bargsten; Yizhou Li; Dario Neri; Mark D Robinson; Constance Ciaudo; Jonathan Hall; Martin Jinek; Gerald Schwank (eLife, 2018)
The CRISPR-Cas9 targeted nuclease technology allows the insertion of genetic modifications with single base-pair precision. The preference of mammalian cells to repair Cas9-induced DNA double-strand breaks via error-prone end-joining pathways rather than via homology-directed repair mechanisms, however, leads to relatively low rates of precise editing from donor DNA. Here we show that spatial and temporal co-localization of the donor template and Cas9 via covalent linkage increases the correction rates up to 24-fold, and demonstrate that the effect is mainly caused by an increase of donor template concentration in the nucleus. Enhanced correction rates were observed in multiple cell types and on different genomic loci, suggesting that covalently linking the donor template to the Cas9 complex provides advantages for clinical applications where high-fidelity repair is desired.